CNSL Concentration and Natural Dyes Effects in Formulation of Botanical Pesticide on Sitophilus zeamais and Maize Seed Quality - Dian Astriani; Wafit Dinarto; Aji Jatmiko (SEAS (Sustainable Environment Agricultural Science), 2020)
Maize is an important commodity in Indonesia and is vulnerable to maize weevil (Sitophilus zeamais) during storage which can cause a 100% yield loss. Chasew Nut Shell Liquid (CNSL) is a botanical pesticide able to control S. zeamais. Increasing CNSL efficiency and effectiveness requires additional adjuvants, such as solvents and dyes. Natural dyes addition is intended to provide seed markers. This study aimed to determine the best CNSL and natural dye formulation to control maize weevil and maintain maize seeds quality during storage. The research was conducted from August to October 2018 at the Agronomy Laboratory, Faculty of Agroindustry, Yogyakarta Mercu Buana University. The research was a single factor consisted of seven treatments with four replications arranged in a completely randomized design (CRD). Treatments were combinations of CNSL concentrations with the addition of natural dyes from suji leaf and teak leaves with one untreated control. The results of the research showed that CNSL as a seed treatment botanical pesticide could cause mortality and suppress S. zeamais populations and maintain the quality of maize seeds during storage for 12 weeks. Treatments with 20% CNSL formulation concentration and the addition of natural dyes both leaf pleomele or teak leaves could cause higher mortality and push down more populations and also could better maintain seed quality than 10 and 0% CNSL formulation concentrations.